PD-1 and LAG-3 as early prognostic markers in the treatment of patients with chronic lymphocytic leukemia - O. N. Selyutina; I. B. Lysenko; N. K. Guskova; I. А. Novikova; E. Yu. Zlatnik; T. F. Pushkareva; N. V. Nikolaeva; I. A. Kamaeva; E. A. Kapuza; Ya. S. Gaysultanova; L. Ya. Rozenko (Онкогематология)
Background. Recently, studies have been conducted all over the world to study the role of immune checkpoints in the pathogenesis of chronic lymphocytic leukemia (CLL) and the possibility of their use as prognostic markers. Of greatest interest are PD-1 (programmed cell death-1) and LAG-3 protein (lymphocyte-activation gene 3).Aim. To study the features of PD-1 (CD279) and LAG-3 (CD223) expression on blood B-cells of CLL patients and the possibility of their use as early markers for predicting the hematological response to therapy.Materials and methods. The blood of 30 patients with CLL in stage C according to Binet and 20 healthy individuals was studied by 10-color flow cytometry.Results. In patients with CLL, there were significant differences in the initial lymphocytes level, PD-1 and LAG-3 expression on B-lymphocytes, both with persons in the control group and among themselves with different hematological responses to therapy with rituximab according to the results of minimal residual disease monitoring.Conclusion. PD-1 and LAG-3 can be used as early markers for predicting the response of CLL patients to therapy. The combined use of initial lymphocytes level and PD-1 and LAG-3 expression on CD19+ blood cells has a greater prognostic value. New data obtained from the study of immune checkpoints PD-1 and LAG-3 may be useful in the development of targeted therapeutic agents.